EFEKTIVITAS PERAN SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PEDAGANG KAKI LIMA DI KOTA BANDUNG - Maris Gunawan Rukmana (Jurnal Tatapamong, 2020)
The Civil Service Police Unit (Satpol PP) is an organization that has quite strategic tasks, functions and authorities in organizing the enforcement of regional regulations and decisions of the Head of the Region, Organizing public peace and order, and community protection. The city of Bandung as the capital of West Java Province which has the potential as a destination area for immigrants to meet the living needs of various areas to complain about fate. Thus, as a trade destination area, it is necessary to arrange an orderly, comfortable and peaceful situation for the people of Bandung City. Street vendors are one of the informal livelihoods that are mostly located in every corner of Bandung City. In addition to having a source of income for the area, but on the other hand is another problem for the government of Bandung City. The purpose of writing is to find out how the effectiveness of the role of the Civil Service Police Unit in Disciplining Pedestrian Traders in the City of Bandung. The method used in this writing is Descriptive Analysis by using research tools in the form of literature study on the Effectiveness and Role of Civil Servants Unit (Satpol PP).